Emergency Supply Control from the Perspectives of Peacetime and Wartime: A System Dynamics Simulation - Yuqing Qi; Xinglei Zhao; Heba El-Sayed; Bin Wu (Complex System Modeling and Simulation, 2021)
The supply of emergency materials is the fundament of emergency rescues. In view of the demand for emergency materials in major calamities, in this paper, a system dynamics model of emergency materials is constructed from the perspectives of wartime and peacetime. By setting and controlling the relevant parameters and variables, the influence of a variable on the demand and supply of emergency materials and the influence of government strategies on the quantity and provision of emergency material supply are analyzed. We explore the measures that can better ensure the supply to stabilize the social and economic security of the country. The results show that the emergency degree of an event will lead to increases in the amount of government expenditures and in the duration of such expenditures. Meanwhile, the increase in emergency cases will increase the variation range of the supply and demand deviation curve, lengthen the response time to demand, and fasten the growth trend of material supply. The Chinese government adopts comprehensive regulation and control mode, which make the supply and demand reach the equilibrium state more than twice as fast as other control methods. In addition, the promotion of publicity will improve the number of civil materials. A high inflation rate will lead to high imports of government materials, which will consequently affect the supply of emergency materials. The above research findings have important reference significance for the government’s emergency materials management.